2017
DOI: 10.1016/j.neuropharm.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The binding orientation of epibatidine at α7 nACh receptors

Abstract: Epibatidine is an alkaloid toxin that binds with high affinity to nicotinic and muscarinic acetylcholine receptors, and has been extensively used as a research tool. To examine binding interactions at the nicotinic receptor, it has been co-crystallised with the structural homologue acetylcholine binding protein (AChBP; PDB ID 2BYQ), and with an AChBP chimaera (3SQ6) that shares 64% sequence identity with the α7 nACh receptor. However, the binding orientations revealed by AChBP co-crystal structures may not pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The marine mollusk Aplysia californica expresses a watersoluble protein called AChBP that functions to modulate AChmediated synaptic transmission in this organism (31). X-ray crystallography studies of the AChBP have been used to elucidate binding interactions between ligands and nAChRs (32)(33)(34)(35). Several high-resolution crystal structures have been reported for the AChBP complexed with ␣-Ctxs (36 -39) but not with PeIA.…”
Section: X-ray Crystallography Of Peia Complexed With Aplysia Califormentioning
confidence: 99%
“…The marine mollusk Aplysia californica expresses a watersoluble protein called AChBP that functions to modulate AChmediated synaptic transmission in this organism (31). X-ray crystallography studies of the AChBP have been used to elucidate binding interactions between ligands and nAChRs (32)(33)(34)(35). Several high-resolution crystal structures have been reported for the AChBP complexed with ␣-Ctxs (36 -39) but not with PeIA.…”
Section: X-ray Crystallography Of Peia Complexed With Aplysia Califormentioning
confidence: 99%
“…The results show that their orientations differ, and question whether it is appropriate to use these receptor homologues for predicting ligand binding at different members of the Cys-loop family (Thompson et al., 2017). …”
Section: Introductionmentioning
confidence: 99%
“…However, little assessment has been done about some critical aspects of their conformational variability (15, 59). Recently, the crystallographic structure of the extracellular domain of the nicotinic receptor α7 in complex with epibatidine was reported (60). Although the interactions described for this complex agree with our results, it was found that the residues THR146, CYS187, and CYS186 could also be involved in the protein complex due to their molecular proximity (Fig 2).…”
Section: Discussionmentioning
confidence: 99%